Genital Tuberculosis with Pleuritis and Intra-abdominal Tuberculosis - Widowati, Ayu Rizky; Indrawan, I Wayan Agung; Tantular, Rezki (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Female Genital Tuberculosis (FGTB) is a rare but serious form of extrapulmonary tuberculosis that significantly impacts female reproductive health. It accounts for 15–20% of extrapulmonary TB cases and is found in 5–10% of infertile women. Diagnosis is often delayed due to nonspecific symptoms and the difficulty of confirming infection through histopathology. Case Presentation: A 35-year-old woman presented with abdominal pain, nausea, vomiting, vaginal discharge, and postcoital bleeding. A cervical biopsy confirmed tuberculous cervicitis, supported by systemic TB symptoms and a left pleural effusion, leading to a diagnosis of extrapulmonary TB. She was treated with a full course of anti-TB therapy and referred for fertility evaluation due to persistent amenorrhea, where hysteroscopy revealed intrauterine adhesions and granulomas, confirming suspected genital TB and suggesting Asherman’s syndrome as a complication. Conclusion: Female Genital Tuberculosis is a rare cause of infertility; early diagnosis using integrative methods and awareness of genital TB transmission are essential for timely treatment and improved reproductive outcomes.